A Study of the Effect of some of Salix emophylla Extracts as a Mulcicide to the snail Bulinus truncatus the Intermediate Host of Schistosoma Haematobiun - Mohammed J. Al-Obaidy; Acmam Ali (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2026)
Salix acmophylla extracts used as a mulcicide to the snail Bulinus truncatus the intermediate host of Schistosoma haematobium in Iraq to know the acute toxicity of these extracts. The study showed acute toxicity of leaves and bark extracts to the snail and the leaves extracts less toxic than the bark extracts. LC50 of leaves extracts 20gm/1) was 7% while the LC50 bark extracts 10gm/l) was 8%.There was a relationship between the time of study showed the ability to use the bark and leaves extracts in the exposure and the concentrations of bark and leaves extracts . This control of schistosomiasis synthesis and Characterization of Some Lanthanidel (II) Ions Complexes with Anthranilic Acid and Amino Acid Phenylalanine